A poesia precursora do modernismo em Sergipe - Oliveira, Edna Caroline Alexandria da Cunha (2022)
This work aims to map the events that contributed to the dissemination of Modernism in Sergipe, with regard to poetic production, between 1920 and 1930, in the context of the modernization of Aracaju, a newly established capital that gained an air of urbanization and beautification in the first decades of the twentieth century. Our corpus consists of publications in newspapers that circulated at the time, among which we highlight for this thesis: O Estado de Sergipe, A República, Diário da Manhã, Gazeta de Sergipe, Diário de Sergipe, O Nordeste, Gazeta do Povo, Jornal do Povo, Sergipe-Jornal and the Boletim Liberal between the years 1922 to 1933. We also consulted the newspapers A Razão and O Piauhytinga, from the municipality of Estância, between the years 1926 to 1930. Our historical sources also include the magazine Renovação (1931-1934). The materiality is composed of modern poems, dissemination of literary events, manifestos, editorials, opinion articles, interviews, postcards, letters, magazines inserted in the new aesthetics, fascicles, books and, above all, the poems published by the precursors of the modernist aesthetics in Sergipe. To this end, the work is divided into four parts. In the first part we describe the movement of the creators of modern poetry in Sergipe that culminated with the realization of the 29th Night, an event that adhered to modernist ideas; in the second part we situate the reception of the modern spirit among the young poets from Sergipe who defended the new thought; in the third part we present the magazine Renovação and the emergence of the voice of women through the experience of creative literary writing present in each edition of this periodical; finally, in the fourth part we bring together the poetic work of Abelardo Romero and José Maria Fontes considered by the local critics as those who, in fact, reverberated the modernist aesthetics in Sergipe. The following were in favor of the new aesthetic: Heribaldo Vieira, Carlos Fontes, João Passos Cabral, Maria Rita Soares de Andrade and the modern poets Abelardo Romero and José Maria Fontes, the latter two being the creators of the Night of 29, so we dedicated a critical reading to the poetic work of both writers. Among the works that support the course of our investigation through the Sergipe newspaper library - taking as a starting point the collection of the literary critic, folklorist and researcher of Sergipe History and Culture, Jackson da Silva Lima, are: Poesia sergipana, uma antologia (OLYNTHO, 1988); Literatura sergipana (ARAÚJO, 1976); Vida literária (SOUZA, 1961); Jordão de Oliveira (RIBEIRO, 2006); Agremiações culturais de jovens intelectuais na imprensa estudantil (GILFRANCISCO, 2019); Revistas do IHGSE (1919- 1951); História de Sergipe: República (1889-2000) (DANTAS, 2004); Álbum de Sergipe: 1820 a 1920 (SILVA, 1920); Álbum photographico de Aracaju (CASA AMADOR, 1931). To deepen the dialogue between Being and Poetic Making in modernity, we brought the thought of Hugo Friedrich, in Estrutura da lírica moderna (1978), characterizing the stylistic transformations and ruptures of modernist poetry. With Émil Staiger (1997) we broadened the debate on modern lyricism between structures, meanings and the constitution of poetic language. In this perspective, Octavio Paz, in O arco e a lira (1982), leads us to think about poetry and poetic work through a critical reading of its components, bringing together language, rhythm and image, consolidating the poetic experience by the presence/function of poetry. With Alfredo Bosi, in the book O ser e o tempo da poesia (1977), we point out the word-image relationship in poetry. In addition to these dialogues, the investigation on poetry and poetic making continues with the essay repertoire proposed by Antonio Cicero, in the book A poesia e a crítica (2017), which makes evident how poetic perceptions are always original, through the way in which the poet feels the world around him. In this way, we reconstruct a considerable amount of information that indicates Sergipe's participation in Modernism – in the understanding of the events and their unfolding, highlighting both the artistic-literary ruptures and the attempts to split the patriarchal models defending the obsolete past that resisted the sociocultural transformations, consequences of the advent of the 20th century.